DEVELOPMENT OF A WEB-BASED FRAMEWORK IN QUEST FOR HIGH IMPACT ONLINE RESEARCH JOURNAL - FROILAN D. MOBO (International Journal on Orange Technologies, 2021)
Most Authors are victims of fake or predatory online journal trying to find out later that their submitted manuscript was published in a blacklisted or fake journal that som that they are indexed in a high impact journal such as Scopus, Web of Science and ISI. For the new authors who are starting with their career in Research and Publication they must be aware of the following situations that there are also fake or predatory online journals that are requested for Call of Papers for Publication. Furthermore, that Researcher is proposing of developing a Web-Based Framework that can detect or measured the impact of a certain Online Research Journal. With this type of study all authors will not be able to encounter these kind of problems and anomalies in Publications and will be able to submit manuscripts to the high impact journal in a much easier and faster way.